Analisis Perilaku Positif Deviance Pemberian Makan dan Ketahanan Pangan Keluarga Miskin - Saragih, Bernatal (Jurnal Magrobis, 2014)
Background. Food is an essential and strategic commodity for Indonesia because food is a basic human need that must be met by the government and society . Impact on poverty and access to food purchasing power and will of course also a hedge against the nutritional status of the family in society. Objectives . To analyze the behavior of mothers positive deviance in feeding and food security of poor families. Methods . This study was conducted with a cross-sectional design is qualitative in maternal informants as positive deviance actors where poor families and have a well-nourished child . Research carried out each 4 RT in Samarinda and 2 RT and 2 village in Kutai Timur Regency. Data analysis by desctiptive.. Results . Average nutritional status (z-score) was -0.3.. Mother provide food menu based on availability and preferences of toddlers . The main information obtained mother in determining the variety of food from posyandu, other than that of the medium of television , friends and parents/in-laws . Mom has a persistent effort to overcome the problem of appetite in infants , especially during illness chiefly with children easily swallowed foods like porridge . Although the mothers of poor families also have offender Positive Deviance household food security is good . Conclusion . Feeding with coax children than with balanced nutrition is the strategy most often performed by maternal.Key words: positive deviance, nutrition status, food security